Kemampuan Laba dan Arus Kas Dalam Memprediksi Laba dan Arus Kas Masa Mendatang Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2013- 2016 - Heru Budiono; Noor Shodiq Askandar; Afifudin Afifudin (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this research is: 1) to know the earnings and cash flow capability topredict the earnings in the future, 2) to know the earnings capability and cash flow to predictthem in the future, 3) to know the predict capability incremental cash flow of the future.The research used the sample of the manufacture companies listing on IndonesiaStock Exchange and research period of 2013-2016. The sample obtained of 38manufacturing companies trantumed in Indonesia Stock Exchange. T he variables of theresearch are independent variables that consist earnings and cash flows of the previousperiod, while the dependent variables are the future of earnings and cash flows. Thisresearch used a double regression linear.The result of the test show that earnings and cash flow has the ability to predictingearnings in the future. Profit and cash flow have the ability to predict them in the future.Earnings and cash flows alike have an incremental predictive capability for them in thefuture.Keyword : Manufacture Company, Earnings, Cash Flow, Prediction Capability.